On Upper Bias in ’Forest Cover’ Data of Hilly Terrain Obtained through Satellite Imagery with Special Reference to Mizoram - Jha, Sanjeeva Kumar (Indian Forester, 2001)
The high intensity of slope of hills in Mizoram causes a significant degradation in the ground resolution of the sensor of a satellite. Consequently, the intensity of the corresponding picture element gets increased in favour of higher canopy density class owing to the adequacy in the natural vegetational growth in the State. Hence, during cover classification stage, an upper bias is introduced. The present paper tries to investigate and measure the bias.